Blue Sukuk: Inovasi Pembiayaan Syariah untuk Konservasi Kelautan Berkelanjutan tinjauan Maqashid syariah - Umar Syahid; Siti Achiria (UIN AM. Sangadji Ambon, 2025)
Significant financial support is needed to optimize the marine economy for future food sources, energy security, and public welfare. To promote the blue economy in Indonesia, the government must create financial instruments. Encouraging public investment in this industry through government-provided instruments, such as sovereign sukuk, is one creative funding source that can be explored. The purpose of this research is to explore blue sukuk through the lens of maqasid sharia.This research is a descriptive qualitative study using a conceptual approach.The results indicate that improving the quality of marine ecosystems aligns with the objectives of Fiqh al-Biah, or maqasid sharia, namely protecting the environment, including marine ecosystems, and is consistent with the concept of the Blue Economy. The Blue Economy concept has emerged as a solution for appropriate and sustainable coastal development. The Blue Economy concept aims to promote economic growth, social inclusion, and preservation of marine ecosystems, while improving livelihoods by ensuring environmental sustainability.